164k views
3 votes
(x+7)1/3=(9x)1/3

(x + 7) (1)/( 3) = (9x) (1)/(3)

User Pamba
by
6.6k points

1 Answer

6 votes
The first step for solving this equation is to distribute
(1)/(3) through the first set of parenthesis.

(1)/(3)x + (7)/(3) = (9x) ×
(1)/(3)
Remove the parenthesis.

(1)/(3)x + (7)/(3) = 9x ×
(1)/(3)
Reduce the numbers on the right side of the equals sign with 3.

(1)/(3)x + (7)/(3) = 3x
Now multiply both sides of the equation by 3.
x + 7 = 9x
Move the constant to the right side and then change its sign.
x = 9x - 7
Move the variable to the left side and change its sign.
x - 9x = -7
-8x = -7
Lastly,, divide both sides of the equation by -8 to find your final answer.
x =
(7)/(8)
Let me know if you have any further questions.
:)
User Siddharth Shukla
by
6.0k points